Compact variation, compact subdifferetiability and indefinite Bochner integral - Stonyakin, F. S.; Orlov, I. V. (Methods of Functional Analysis and Topology, 2009)
The notions of compact convex variation and compact convex subdifferential for the mappings from a segment into a locally convex space (LCS) are studied. In the case of an arbitrary complete LCS, each indefinite Bochner integral has compact variation and each strongly absolutely continuous and compact subdifferentiable a.e. mapping is an indefinite Bochner integral.